The Use of Songs in Increasing Students’ Understanding of Figurative Language - S Salwa; Ayu Liskinasih (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2016)
ABSTRACT This study aims at investigating the perceptions of students at Kanjuruhan University of Malang about the use of songs as supplementary materials in understanding the meanings of figurative language such as metaphor, hyperbole, personification, etc. This study employed a mixed-methods approach. The data were collected through questionnaire, video-recording and focus-group discussion. The participants of this study were 30 students attending vocabulary class in the third semester. The results of this data analysis showed that most of the students (85%) have positive attitudes towards the use of songs as considerable media to help them understand the meanings of figurative language and improve their motivation in learning English. It is hoped that English lecturers will use songs as one of interesting techniques in teaching figurative language, so that students will be more interested in analyzing figurative language using authentic-based materials. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan secara rinci bagaimana pembelajaran bahasa kiasan (figurative language) seperti metafora, hiperbola, personifikasi, dsb agar dapat lebih mudah dimengerti oleh para mahasiswa, melalui media lagu sebagai materi tambahan (supplementary materials). Metode penelitian ini adalah mixed-method. Peneliti menggunakan beberapa instrumen penelitian yaitu kuesioner, observasi, rekaman video dan juga focus- group discussion yang dilakukan pada para participant yaitu 30 mahasiswa semester tiga yang menempuh mata kuliah Vocabulary pada jurusan pendidikan Bahasa Inggris Universitas Kanjuruhan Malang. Hasil dari penelitian ini menunjukkan bahwasanya para mahasiswa (85%) memiliki persepsi dan sikap yang positif terhadap penggunaan lagu dalam pembelajaran Figurative language. Pembelajaran dengan menggunaan media lagu ini juga dapat meningkatkan motivasi mahasiswa dalam mempelajari Figurative language. Penelitian ini secara teori dapat menambah variasi metode pembelajaran Figurative language sehingga diharapkan para dosen pengajar mata kuliah vocabulary serta mata kuliah Intro to literature (pendekatan sastra) dapat menerapkan metode ini didalam kelas sehingga dapat meningkatkan motivasi mahasiswa dalam mempelajari bahasa Inggris sebagai bahasa asing melalui media otentik seperti lagu. How to Cite: Salwa. Liskinasih, A. (2016). The Use of Songs in Increasing Students’ Understanding of Figurative Language. IJEE (Indonesian Journal of English Education), 3(1), 75-88. doi:10.15408/ijee.v3 i1.3443 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.3443